An Investigation on Sheeting Acting as a Diaphragm on a Reinforced Precast Concrete Frame - Țere, Sergiu-Gheorghe; Hegheș, Bogdan; Constantinescu, Horea (Periodica Polytechnica Civil Engineering, 2020)
It is well-known that for single-storey steel structures, the framework is greatly strengthened and stiffened following the attachment of the roof, floors and walls. The panels in the roofing, flooring and side cladding are also known as “shear diaphragms” by virtue of their resistance to being deformed into parallelograms. This has been verified by on-site practical experience of many structures and design provisions are available for structural engineers. Despite the fact that for single-storey structures, the corrugated steel sheets are the standard elements in constructing the envelopes, in what concerns the reinforced concrete frames there are no guidelines nor recommendations on how to consider the diaphragm effect in structural analysis. In order to better understand the interaction between the corrugated steel sheets and the reinforced concrete frame, a real precast reinforced concrete frame structure was built for experimental testing. The aim of the experimental test is to study the diaphragm effect for reinforced concrete structures and based on the results to identify the discrepancies identified compared to steel structures. The investigation attempts to provide a starting point for future research on the stressed skin design acting on reinforced concrete frames. At the end of the article conclusions are drawn based on the experience obtained during the experimental test.